Adverse reactions to Pfizer‐BioNTech vaccination of healthcare workers at Malta's state hospital. Issue 10 (19th July 2021) - Cuschieri, Sarah; Borg, Michael; Agius, Steve; Souness, Jorgen; Brincat, Andre; Grech, Victor
Abstract: Background: The long‐term control of COVID‐19 depends on an effective global vaccination strategy. Protecting healthcare workers (HCWs) from serious infection is critical. Malta, a European country, initiated the vaccination roll‐out using Pfizer‐BioNTech COVID‐19 vaccine targeting HCWs. This study determined vaccination adverse effects (AEs) in this cohort. Method: An online survey was disseminated to all HCWs via work email (29/3/21 to 9/4/21) to gather AEs regarding pain, redness and swelling at injection site, fever, chills, fatigue, muscle/joint pains, headache, vomiting and diarrhoea severity following each dose (Likert scale). Descriptive, comparative and multiple binary regression analyses were performed. Results: A response of 30.30% (n = 1480) was achieved with the commonest AEs being pain at injection site (88.92% CI 95%: 87.21‐90.42), mostly mild (51%) and moderate (43%). Fatigue was reported by 72.97% (CI 95%: 70.65‐75.17), 42% were mild and 41% were moderate. Females reported significantly ( P ≤ .05, respectively) more pain (OR: 1.90), redness (OR: 2.49), swelling at injection site (OR: 1.33), fever (OR: 1.74), chills (OR: 2.32), fatigue (OR: 2.43), muscle (OR: 1.54) and joint pains (OR: 2.01), headache (OR: 2.07) and vomiting (OR: 3.43) when adjusted for age and HCW role. Localised AEs were reported following both vaccine doses unlike systemic AEs that were mostly reported after second doses. Conclusion: Vaccination benefits outweigh the minor AEs experienced, with females exhibiting a higher susceptibility. The general low vaccination AEs observed within the HCW cohort is encouraging and should help in allaying vaccine hesitancy among the population.